Caffeic acid phenethyl ester protects rabbit brains against permanent focal ischemia by antioxidant action: A biochemical and planimetric study - Altug, Muhammed Enes; Serarslan, Yurdal; Bal, Ramazan; Kontas, Tuenay; Ekici, Fatih; Melek, Ismet M.; Duman, Taskin (Elsevier, 2008)
The present study was conducted to investigate whether caffeic acid phenethyl ester (CAPE), an active component of propolis extract, has a protective effect on brain injury after focal permanent cerebral ischemia, and to determine the possible antioxidant mechanisms. Cerebral infarction in adult male New Zealand rabbits was induced by microsurgical procedures producing right focal permanent middle cerebral artery occlusion (pMCAO). CAPE was administered to the treatment group after pMCAO at a dose of 10 mu mol kg(-1) once a day intraperitoneally for 7 days. Neurological deficits were evaluated, using a modified six-point scale. Spectrophotometric assay was used to determine the contents of malondialdehyde (MDA), glutathione (GSH), catalase (CAT), nitric oxide (NO) and xanthine oxidase (XO). In the ipsilateral hemisphere, the infarct volume of the brain was assessed in brain slices stained with heamatoxylen and eosin. The results showed that treatment with CAPE significantly reduced the percentage of infarction in the ipsilateral hemisphere compared with the ischemia group. CAPE treatment significantly attenuated the elevation of plasma MDA, CAT and XO content (p < 0.05), whereas it significantly increased the levels of plasma GSH and NO (p < 0.05). Therefore, subacute CAPE administration plays a protective role in focal pMCAO due to attenuation of lipid peroxidation and its antioxidant activity. All of these findings suggest that CAPE provides neuroprotection against cerebral ischemia injury through its antioxidant action. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: caffeic acid phenethyl ester; antioxidant activity; focal permanent cerebral ischemia; neuroprotection; rabbit